Late Referral of Eisenmenger Syndrome in Pregnancy at Dr. Soetomo Hospital Surabaya - Ali Abdat, Amira; Yusuf, Muhammad (Jurnal Medis Islam Internasional, 2020)
Background: Pregnancy with Eisenmenger syndrome is an obstetric problem which numbers keep rising every year. The cases require specific,decisive,and multidisciplinary approach.The unavailability of accurate diagnostic procedures, as well as the national consensus that has not been agreed on, all contributes to the increasing number of late referral that cause morbidity and the high risk of mortality. Purpose:  To know number and cause of late referral cases with Eisenmenger syndrome at Dr. Soetomo General Hospital, Surabaya in 2018-2019. Methods: Retrospective study by using medical records data of Dr. Soetomo General Hospital, Surabaya on January 2018- December 2019. Result: There are 18 cases of Eisenmenger syndrome from January 2018 to December 2019. Approximately 3 cases are timely referral while 15 cases are late referral cases. From those 15 late referral cases, about 12 cases (80%) are pregnant. Based on the risk factors, 73% of the patients have a congenital heart disease (Atrial septal defect) and severe pulmonary hypertension. In the postpartum referral cases group, 3 cases were referred because of suspected heart disease postpartum. Nearly all of the late referred cases have a bad prognosis those maternal deaths. There were 7 maternal deaths caused by cardiogenic shock. Regarding the source of referral, the majority of referred pregnant patient comes from out of Surabaya (73%), while for the postpartum patient, 13 % was referred from out of Surabaya.  According to the referral types, the majority of the late referral cases are emergency referral (73%), as for the postpartum referral, 20% are emergency referral. Conclusion: The number of late referral in Eisenmenger syndrome in Dr. Soetomo general hospital is still high. Further socialization and trainings regarding the early detection and management of Eisenmenger syndrome is still very much needed.